Categorizations of physical gesture in piano teaching: A preliminary enquiry. (January 2015) - Simones, Lilian; Schroeder, Franziska; Rodger, Matthew
The significance of the "physicality" involved in learning to play a musical instrument and the essential role of teachers are areas in need of research. This article explores the role of gesture within teacher–student communicative interaction in one-to-one piano lessons. Three teachers were required to teach a pre-selected repertoire of two contrasting pieces to three students studying piano grade 1. The data was collected by video recordings of piano lessons and analysis based on the type and frequency of gestures employed by teachers in association to teaching behaviours specifying where gestures fit under (or evade) predefined classifications. Spontaneous co-musical gestures were observed in the process of piano tuition emerging with similar general communicative purposes as spontaneous co-verbal gestures and were essential for the process of musical communication between teachers and students. Observed frequencies of categorized gestures varied significantly between different teaching behaviours and between the three teachers. Parallels established between co-verbal and co-musical spontaneous gestures lead to an argument for extension of McNeill's (2005) ideas of imagery–language–dialectic to imagery–music–dialectic with relevant implications for piano pedagogy and fields of study invested in musical communication.